2004
DOI: 10.1007/s00248-004-0031-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variation in Streptomyces Genetic Composition and Diversity in a Prairie Soil

Abstract: Understanding how microbial genotypes are arrayed in space is crucial for identifying local factors that may influence the spatial distribution of genetic diversity. In this study we investigated variation in 16S rDNA sequences and rep-PCR fingerprints of Streptomyces stains isolated from prairie soil among three locations and four soil depths. Substantial variation in Streptomyces OTU (operational taxonomic unit) and BOX-PCR fingerprint diversity was found among locations within a limited spatial area (1 m 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 71 publications
(77 reference statements)
1
31
0
Order By: Relevance
“…Therefore, antibiotic activity is a practically and ecologically important trait of these microorganisms. In previous research, we have found the spatial localization of antibiotic inhibitory and resistance phenotypes between locations (Davelos et al , 2004a), as well as the spatial localization of genetic groups and variation in genetic diversity between locations (Davelos et al , 2004c).…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, antibiotic activity is a practically and ecologically important trait of these microorganisms. In previous research, we have found the spatial localization of antibiotic inhibitory and resistance phenotypes between locations (Davelos et al , 2004a), as well as the spatial localization of genetic groups and variation in genetic diversity between locations (Davelos et al , 2004c).…”
Section: Introductionmentioning
confidence: 97%
“…Even in such cosmopolitan bacteria, there are local ecotypes that are unrelated to any other known strains (Gonzalez-Gonzalez et al, 2013; Avitia et al, 2014; Valdivia-Anistro et al, 2015). Streptomyces , a filament and spore producer, and the most extensively studied genera of Actinomycetes, has been studied and it had shown environmental gradients and regional endemism in some localities (Davelos et al, 2004; Antony-Babu, Stach & Goodfellow, 2008; Kinkel et al, 2014; Andam et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that bacteria can exhibit patterns in taxonomic diversity and community composition similar to those of plants and animals (e.g., Horner-Devine et al 2003, 2004b. However, most of these studies have relied on measures of diversity that do not consider phylogenetic relatedness (Bohannan and Hughes 2003), and few studies have quantitatively examined bacterial communities within a phylogenetic context (Martin 2002, Davelos et al 2004.…”
Section: Introductionmentioning
confidence: 99%